A SYSTEMATIC ANALYSIS OF AI-EMPOWERED EDUCATIONAL TOOLS DEVELOPED IN INDIA FOR DISABLED PEOPLE - Shivani; Monika Gupta; Satinder Bal Gupta (Інформаційні технології і засоби навчання)
Artificial Intelligence (AI) plays a multifaceted role in educating impaired people and has significantly enhanced the learning experience of disabled students. AI is emerging as an influential tool that enhances accessibility, personalizes the learning process, and promotes inclusivity in educating students with disabilities. For visually disabled students, AI-powered braille devices help the children learn and rehearse braille independently. AI can be incorporated into mobile applications and learning platforms invented to help dyslexic students in India. These apps provide many features to make learning fun for learners with disabilities. The Notebook platform utilizes Machine Learning algorithms that provide students with a personalized learning experience. AACDD makes the process of learning easy for children suffering from neuro-developmental disorders. Augmenta11y app utilizes AR (Augmented Reality) to display the content in a form that dyslexic children can easily understand. DYSXA app provides many features for making learning fun for learners with disabilities. Using automation and the latest technologies, Stamurai provides speech therapy to such people at a meager cost. The authors have analyzed and discussed more AI tools developed to help disabled students with education. With the use of these tools, children with disabilities can communicate better, receive an inclusive education, be more accessible, be mentally prepared, and lead independent lives. These tools have shown promising potential in supporting children with disability. It is observed that AI holds much potential to strengthen the learning experiences of disabled students by providing them with personalized support and alleviating the difficulties they face in reading, writing, and learning a language with accuracy.